Integrin regulation of epidermal growth factor (EGF) receptor and of EGF-dependent responses. (1st June 2004) - Cabodi, S.; Moro, L.; Bergatto, E.; Boeri Erba, E.; Di Stefano, P.; Turco, E.; Tarone, G.; Defilippi, P.
Abstract : Integrin signalling co-ordinates with signalling originating from growth factor receptors in the co-operative control of cell proliferation, survival and migration. Increasing evidence suggests that integrins form physical complexes at the cell membrane with growth factor receptors, giving rise to signalling platforms at the adhesive sites. It is probable that at these sites integrins regulate adhesion and at the same time physically constrain and direct the response to soluble growth factors towards proliferation or survival stimuli. These co-operative effects might depend on integrin ability to activate growth factor receptors. In the present paper, we summarize our recent study showing that integrin-dependent adhesion triggers ligand-independent EGFR (epidermal growth factor receptor) activation to transduce downstream signalling. In addition, we also show that integrin-induced signalling pathways are necessary for EGF-dependent transcriptional response, demonstrating the requirement of the co-operation between cell–matrix adhesion and EGFR to achieve full biological responses.